2011
DOI: 10.1089/ten.tea.2010.0633
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Rat Sciatic Nerve Gap by a Silk Fibroin-Based Scaffold Added with Bone Marrow Mesenchymal Stem Cells

Abstract: Tissue-engineered nerve grafts (TENGs), typically consisting of a neural scaffold included with support cells and/or growth factors, represent a promising alternative to autologous nerve grafts for surgical repair of large peripheral nerve gaps. Here, we developed a new design of TENGs by introducing bone marrow mesenchymal stem cells (MSCs) of rats, as support cells, into a silk fibroin (SF)-based scaffold, which was composed of an SF nerve guidance conduit and oriented SF filaments as the conduit lumen fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 62 publications
2
69
0
5
Order By: Relevance
“…This ability of MSC to potentiate axonal growth has been also described when the cells are transplanted distal to the MN soma. Thus, an increased rate of regeneration by MSC grafts was reported after sciatic nerve transection and repair with synthetic tubes [30] or after facial nerve transection [52]. In our in vitro model, we also observed that MSC enhance axonal regeneration, thus confirming the in vivo findings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This ability of MSC to potentiate axonal growth has been also described when the cells are transplanted distal to the MN soma. Thus, an increased rate of regeneration by MSC grafts was reported after sciatic nerve transection and repair with synthetic tubes [30] or after facial nerve transection [52]. In our in vitro model, we also observed that MSC enhance axonal regeneration, thus confirming the in vivo findings.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, after spinal cord injury [23][24][25][26] and brain stroke [27,28] focal injection of MSC improves functional recovery and reduces tissue damage and neuronal death. Furthermore, in experimental peripheral nerve injuries, MSC grafts have the capacity to enhance axonal regeneration [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular prostheses composed of a resorbable guide seeded with autologous Schwann cells are an alternative for repairing long gaps in injured nerves, approaching the success of autografts [280,281]. However, conduits containing syngeneic Schwann cells did not improve the extent of axon regeneration with respect to acellular guides [280].…”
Section: Schwann Cells and Bone Marrow-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Filling a nerve gap with a 3-dimensional Matrigel promotes axon regeneration entirely across gaps [281,331]. This influence is increased if Schwann cells overexpressing high molecular weight FGF-2 is combined with the Matrigel [287].…”
Section: -Dimensional Scaffoldsmentioning
confidence: 99%
“…In cases where the extent of the lesion precludes the simple joining of the stumps, an available and widely used repair technique is tubulization. This technique, cells include the mesenchymal cells of the bone marrow and of the adipose tissue, as well as the actual Schwann cells (6,7,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) (Table 1). These cells can be applied directly after density gradient separation (Ficoll-Paque ® ) or be cultivated and differentiated in vitro for subsequent application, as is the case of stem cell differentiation into Schwann cells.…”
Section: Introductionmentioning
confidence: 99%